2021
DOI: 10.35942/jbmed.v3i3.206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Influence of Selected Procurement Practices on the Performance of Devolved Government Units in Kenya: A Case of Machakos County Government

Abstract: In the devolved units in Kenya, despite the formulation of strategic plans, majority of the counties remain underdeveloped with the employees remaining reluctant thus citizens’ demand for better services remain un met. The devolved systems of governments in Kenya have also  been experiencing major challenges in the execution of procurement practices. Counties continue to be criticized for corruption cases, stalled projects, under-development and massive wastage of public resources. All these aspects have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…At a 0.000 level of significance, the alternative hypothesis that procurement contract management has a positive impact on the sustainability of stateagencies in Kenya was accepted instead of the null hypothesis. The findings agree with the findings of Mutuku et al (2021), who indicated that management of procurement contract practices improves sustainable performance of devolved governments in Kenya.…”
Section: Regression Coefficients On Procurement Contract Managementsupporting
confidence: 91%
“…At a 0.000 level of significance, the alternative hypothesis that procurement contract management has a positive impact on the sustainability of stateagencies in Kenya was accepted instead of the null hypothesis. The findings agree with the findings of Mutuku et al (2021), who indicated that management of procurement contract practices improves sustainable performance of devolved governments in Kenya.…”
Section: Regression Coefficients On Procurement Contract Managementsupporting
confidence: 91%
“…These differ between business entities and government bodies (Vanneste, 2017). Some of the most important factors include, but not limited to effective Communication, organizational structure, adequate finances, and employee's technical capacity among others (Mutuku & Misango, 2020;Chwira, 2021).…”
Section: Introductionmentioning
confidence: 99%